Clinical Success of Intrauterine Insemination in A Private Fertility Centre (Journal of Chittagong Medical College Teachers' Association, 2020)
Background : IUI is one of the most frequently and widely used therapeutic modalities to treat various forms of infertility. Achieving pregnancy after IUI is presumably due to increase in the number of highly motile spermatozoa with a high proportion of morphologically normal spermatozoa near the site of fertilization. The objectives were to compare the success rates of IUI with that of timed intercourse, compare the success rate of IUI according to the protocols, review methods used to time the IUI with ovulation, identify the factors to determine IUI outcome.Materials and methods : This is a cross sectional prospective study conducted in Surgiscope Fertility Centre, Chattogram, Bangladesh over a period of 21 months from 596 patients who underwent IUI. Multiple variables were selected such patient parameters like age of woman and cause of infertility, parameters related to ovulation induction such as drugs used for COH, number of mature follicles and endometrial thickness and laboratory parameters such as post wash sperm count and type of IUI (Single or double IUI) which were recorded and statistically analysed.Results : The minimum age for females and males were 18 and 19 respectively and the maximum age for females and males were 40 and 66 respectively. The mean age for females was 27.3 +/- 0.4 years and the mean age for males was 35.9 +/- 0.5 years. Another variable was endometrial thickness where the mean was 8.9 mm ± 0.2 mm and median was 8.5 mm. Furthermore, successful pregnancies also depend on total motile sperm count taken post-wash. The total motile sperm count was 29.8 million ± 1.5 million and median was 30 million. Pregnancy rate for total motile sperm count less than 10 million was 8.6%. For women over 28 and total motile sperm count